South Africa's Plan and Capability in the Nuclear Field - United Nations Office for Disarmament Affairs (United Nations, 1981)
This report, submitted to the General Assembly for consideration at its thirty-fifth session, was prepared by the Group of Experts on South Africa's Plan and Capability in the Nuclear Field, which was appointed by the Secretary-General to assist in the preparation of a comprehensive report on that matter, in accordance with Assembly resolution 34/76 B of 11 December 1979. The subject matter falls within the context of denuclearization of Africa, which has been the subject of continuous and active concern in the United Nations since 1961.